Green Business, Green Values, and Sustainability. - Pitelis, Christos (Taylor & Francis, 2011)
Green Business, Green Values, and Sustainability offers a concise and definitive book on the green transformation of business. The book examines the dramatic changes in business values and strategies that have taken place in recent years in response to the sustainability imperative. Government, industry, academic and science leaders spell out the green future for business.